STRATEGIC ANALYSIS OF DEEP LEARNING IMPLEMENTATION IN HIGH SCHOOL GEOGRAPHY EDUCATION: A CASE STUDY FROM SURAKARTA, INDONESIA - Albertus Erico Jerry Krisna Nugroho; Sugiyanto Sugiyanto; Singgih Prihadi (GeoEco, 2026)
The implementation of the Deep Learning Approach in Indonesia’s Merdeka Curriculum marks a significant shift toward competency-based and student-centered learning. However, its implementation in geography education remains uneven and context-dependent. This study aims to analyze the strategic implementation of the Deep Learning Approach in high school geography education through a SWOT-based approach in Surakarta, Indonesia. This study employs a qualitative design with a strategic analysis framework. Data were collected from nine public high schools using observation, in-depth interviews, open-ended questionnaires, and document analysis. Informants included school administrators, geography teachers, and students selected through purposive sampling. Data were analyzed through coding, categorization, and SWOT matrix mapping to formulate strategic directions. Findings indicate that while most schools have established a conceptual foundation for deep learning reflected in curriculum alignment, teacher competencies, and emerging reflective practices its implementation remains inconsistent and largely in a transitional phase. Strengths relate to an adaptive curriculum and pedagogical readiness, while weaknesses include uneven implementation and limited resources. Opportunities arise from strong policy support and professional networks, while threats stem from administrative burdens and exam-oriented pressures. This study also identifies varying implementation trajectories, ranging from basic to advanced levels across different schools. The study concludes that the implementation of the Deep Learning Approach is a complex and multi-layered process, shaped by the interaction between institutional capacity and systemic pressures. Therefore, context-sensitive and differentiated strategies are essential to ensure sustainable and systemic transformation in geography education.